As formas de autoinscrição na moda afro fortalezense - Chagas, Juliana Silva (2021)
This work, of anthropological nature, deals with the relationships established between blackness and fashion in the city of Fortaleza/CE. The research addresses questions about identity and notion of person, from the socio-spatial context and the production and marketing of garments designated by the interlocutors as afro fashion. The first part of the field research is composed of in-depth interviews that I conducted with three Afro fashion producers, Lita Stéphanie, Yasmin Djalo and Patrícia Bittencourt, in which I could investigate their ways of identification as a black person and their relationship with their craft, which they qualify as afroentrepreneurship. The second part of the research takes place in the collaborative store CearAfro, together with its creator and also afroentrepreneur Aliciane Barros, in which I could observe to what extent notions such as diaspora and identity, intertwining with their commercial practices, can be means of accessing and maintaining their bonds of negritude, as well as how afroentrepreneurship, by promoting a permanent contact between afrocentered black people, acts in the strengthening of these.